This is your mind on plants [large type] - Pollan, Michael (Random House Large Print, 2021)
In this unique blend of history, science and memoir, the author examines and experiences three plant drugs--opium, caffeine and mescaline--from several very different angles and contexts, exploring the powerful human attraction to psychoactive plants.